Planar heterojunction Sb2S3 solar cells with inorganic charge transport layers - Adijaya, Aryacitta (Nanyang Technological University, 2020)
Binary compound Sb2S3 is a very promising light harvesting material due to its good stability, appropriate band gap (1.7-1.8 eV) and high light absorption coefficient. A typical n-i-p architecture of FTO/TiO2/Sb2S3/Spiro-OMeTAD/Au is widely adopted for current Sb2S3 solar cell. Nevertheless, there is currently a 20% gap between the current record efficiency of Sb2S3 with the maximum theoretical efficiency, mainly due to the severe interfacial recombination between ETL and absorber, poor crystallinity, and poor charge transport property of the Sb2S3 bulk. In addition, the unstable organic hole transport layer (Spiro-OMeTAD) is also regarded as an obstacle for the large-scale applications of Sb2S3. Considering the role of inorganic matrix in modulating crystal growth, inserting an interfacial layer on top of TiO2 could be a feasible way to control the Sb2S3 crystal growth. It has been proven that CdS and ZnS are suitable n-type layer to form p-n junction with chalcogenide absorber in traditional inorganic compound solar cells. In this project, the effect of inserting thin CdS and ZnS buffer layer between the TiO2 and Sb2S3 layers on the crystal growth of Sb2S3 as well as the final device performance was first investigated. Moreover, this project also successfully fabricated fully-inorganic Sb2S3 solar cells using NiOx as hole transport layer material. The effect of NiOx solution concentration on the NiOx film properties and the overall device performance was also explored. The result obtained from this project showed that the insertion of CdS and ZnS to form a double electron transport layer successfully improved the quality of the Sb2S3 film morphology and crystal orientation, which consequently enhanced the Voc, Jsc, FF, and PCE by 157.69%, 80.31%, 42.24%, 557.90% and 107.69%, 24.32%, 11.70%, 192.11% for CdS and ZnS respectively. However, undesirable interdiffusion in ZnS interfacial layer was also observed. Low temperature Sb2S3 deposition method was proposed as a possible solution. Furthermore, NiOx was successfully deposited on top of the samples, and the NiOx-based devices were able to produce a comparable result compared to those of Spiro-OMeTAD-based devices. However, the conductivity of the NiOx film is still low even in low NiOx solution concentration, due to the low FF value. Post-treatment such as doping was proposed to further improve the conductivity of NiOx.